IMPROVING QUALITY OF EDUCATION: CURRENT ISSUES OF SCIENCE, EDUCATION AND PRODUCTION INTEGRATION - Nazarboyeva Niginabonu (XALQARO ILMIY-AMALIY ANJUMAN "TA'LIM MAYDONI TENDENSIYALARI: KOMPETENTSIYALAR, INNOVATSIYALAR VA TEXNOLOGIYALAR", 2025)
The following article examines the types of method in Uzbek and English and explains their differences and uses. The main content of the article will help students learning English as a second foreign language to fully understand the integration in both languages.